Design considerations for contact-less underwater power delivery: a systematic review and critical analysis. Issue 1 (13th March 2020) - Zhou, Jing; Guo, Kan; Chen, Zhonghua; Sun, Hui; Hu, Sideng
Abstract: Wireless power transfer (WPT) has attracted attention from academia and industry in recent years. WPT has natural electrical isolation between primary and secondary side, which ensures safe charging in an underwater environment. This breakthrough technology greatly facilitates the deep-sea power transmission. However, at the current stage the transferred power and energy efficiency level are not up to that of the WPT system in the air. The major concerns include the attenuation is seawater, extreme temperature and pressure conditions, disturbance of ocean currents, and bio-security. Three questions are answered in this paper: first, the expressions of eddy current loss and attenuation of electromagnetic wave in seawater are unified, and the influence of seawater as transmission medium on the WPT system is discussed. Second, the evolution of electromagnetic coupling structure suitable for underwater applications is studied. Third, the loss and heating effects of an underwater WPT system and the corresponding bio-fouling phenomenon are investigated. The questions above were addressed through analysis of electrical properties, coupler structures, and bio-fouling effects of the underwater WPT system. This paper will facilitate the study and research on underwater WPT applications.